The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2174/1566523219666190618093707
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MDSC and Immune Tolerance in Transplantation: Cytokines, Pathways and Cell-cell Interaction

Abstract: MDSCs play an important role in the induction of immune tolerance. Cytokines and chemokines (GM-CSF, IL-6) contributed to the expansion, accumulation of MDSCs, and MDSCs function through iNOS, arginase and PD-L1. MDSCs are recruited and regulated through JAK/STAT, mTOR and Raf/MEK/ERK signaling pathways. MDSCs’ immunosuppressive functions were realized through Tregs-mediated pathways and their direct suppression of immune cells. All of the above contribute to the MDSC-related immune tolerance in transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 136 publications
0
10
0
Order By: Relevance
“…Recent years, PD1 and PDL1 are hot spots in the immune regulation. Several studies reported that they governed pathways acting as feedback to prevent excessive T cell response ( Yang et al, 2019 ). In this study, the basal-like subtype samples showed higher expression of immune checkpoint genes (PD-L1, PD-L2, CD40, CD80, CD86, IDO1, and LAG3) than other subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years, PD1 and PDL1 are hot spots in the immune regulation. Several studies reported that they governed pathways acting as feedback to prevent excessive T cell response ( Yang et al, 2019 ). In this study, the basal-like subtype samples showed higher expression of immune checkpoint genes (PD-L1, PD-L2, CD40, CD80, CD86, IDO1, and LAG3) than other subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that CCR5 + MDSCs could migrate to the endometriosis lesions 148 and contribute to the progression of endometriosis through enhancing the generation of arginase (ARG-1), indoleamine2,3-dioxygenase1 (IDO), inducible nitric oxide synthase (iNOS) and PD-L1. 149 , 150 The production of ARG-1 might be associated with the consumption of the amino acids that is required for the T cell function, thus, inhibiting T cells in several ways. In addition to that, both IDO and PD-L1 could act as suppressors for T cells.…”
Section: Ccl5/ccr5 and Diseasesmentioning
confidence: 99%
“…The interplay between MDSCs and Tregs contribute to the establishment of an immunosuppressive environment. MDSCs promote the production of Tregs via a cell-contact dependent mechanism, inducing immune tolerance under conditions of cancers or other abnormal immune responses [ 50 , 51 ]. In addition, MDSCs also directly incite tumor-associated macrophages (TAMs) to facilitate immunosuppression [ 52 ].…”
Section: Mdscs As the Main Component Of Cellular Immune Suppressorsmentioning
confidence: 99%